Immunological disturbances in toxic multinodular goitre and active Graves' disease - Kiy, Y.; Rezkallah-Iwasso, M. T.; Peracoli, M. T S; Mota, N. G S (My University, 1982)
Cell-mediated and humoral immunity were studied in seventeen patients with toxic multinodular goitre, ten with active Graves' disease and fourteen healthy controls. The study included determination of sheep erythrocyte and complement rosette-forming cells in peripheral blood, immunoglobulin levels, titres of microsomal antibodies and migration inhibition test using thyroid extract and phytohaemagglutinin. When compared with controls the patients showed a positive response to thyroid antigen in the leucocyte migration inhibition test. Microsomal antibodies were detected in seven out of ten active Graves' disease patients against two out of seventeen of those with toxic multinodular goitre. Significantly increased IgG and IgA and decreased IgM levels were found only in the toxic multinodular group. These data provide further evidence for immunological disturbances in toxic multinodular goitre.
Keywords: immunoglobulin; microsome antibody; endocrine system; etiology; hyperthyroidism; immunity; leukocyte migration inhibition test; major clinical study; toxic goiter; Adult; Aged; Antibody Formation; Cell Migration Inhibition; Female; Goiter, Nodular; Graves' Disease; Human; Immunity, Cellular; Immunoglobulins; Leukocytes; Male; Microsomes; Middle Age; Rosette Formation